RITUAL TOLAK BALA PADA KOMUNITAS ORANG JAWA DI MABAR HILIR - Adelita, Afifa; Ritonga, Sakti; Ismail, Ismail (CV. Kalimasada Group, 2024)
This study aims to see how the process of Rejecting Bala Ritual in Javanese Society and to see the social function that exists in this ritual of rejecting reinforcements. This research was carried out in the Mabar Downstream Village, Medan Deli District, Medan City, North Sumatra. The method used in this research is a qualitative method with a descriptive approach. data sources used are primary and secondary data with key informants as research informants. Data obtained by observation, interview, and documentation methods. researchers use the structure of Functional analysis to see further the problems that exist in the field. Based on the results of this research, it was revealed that the Rejecting Bala Ritual Tradition had existed for a long time, in 1973. And the process of Rejecting Bala Ritual was by way of reciting the word Tauhid, until later at the Penpodo Afnawi Noeh.